Combination of Tripod Position and Pursed Lip Breathing to Reduce Shortness of Breathing in Patients with Respiratory System Disorders - Wiratama, Rahardyan Dika; Rochmah, Ardianti Fauziah; Puspita, Uci Nurhayati; Muhith, Abdul; Zahro, Chilyatiz; Muthoharoh, Anies; Mahyuvi, Tata; Fatkan, Moch (Chakra Brahmanda Lentera Institute, 2024)
Background: Shortness of breath that is not treated immediately will result in several other health problems and threaten death. There are non-pharmacological treatments, namely tripod position techniques and pursed lip breathing. To determine the effectiveness of tripod position and pursed lip breathing on reducing shortness of breath in patients with impaired systems and respiration. Methods: The study design used in this case study is based on evidence-based practice of nursing (EBN) with sampling according to inclusion criteria of 5 respondents—ameasuring instrument used for the assessment of shortness of breath using oxygen saturation observation sheets. Respondents' intervention used SOPs for tripod position and pursed lip breathing. Results: Based on interventions that have been performed on patients, most oxygen saturation < 95% to 80%. Then, after the intervention, there was an increase in oxygen saturation to 96-100% as much as 100%, from the results of the spss test using the Wilcoxon test, p values (0.04) < (0.05) were obtained, which means that there is an effect of the application of tripod position and pursed lip breathing on reducing shortness of breath in patients. Conclusion: Tripod position and pursed lip breathing techniques can reduce shortness of breath in patients. This application can be done independently for 10-15 minutes, as much as two times, to reduce shortness of breath if you experience a recurrence.